Knowledge and attitude of patients and their relatives towards electro-convulsive therapy: a study from a tertiary care centre in Northern India - Kawoos, Yuman; Wani, Zaid Ahmad; Shah, Irfan Ahmad; Rather, Yasir Hassan; Zarger, Waris Ahmad; Amin, Rehana (International Journal of Research in Medical Sciences, 2017)
Background: Electro-convulsive therapy (ECT) has been effective in various psychiatric disorders and is life-saving in some conditions. Despite its effectiveness and lack of serious side-effects, its use is restricted due to negative attitude of patients and their relatives towards ECT. The objective of the study was to study the attitude of patients and their attendants towards ECT. Also, we studied their knowledge regarding ECT prior to the administration of ECT. Methods: A 16 item questionnaire was formulated to be used for assessing the attitude and knowledge about ECT and was administered after translating it into Urdu language for better understanding. Patients planned for ECT were administered the questionnaire after taking consent. A total of 60 patients and 60 attendants were taken up for the study. Results: About 60-70% of patients gave correct (right) responses to questions like ECT being life-saving procedure, need of investigations before ECT and other questions like question numbers 1,5,6,7,11,14,15. There was little knowledge regarding other areas like use of ECT in pregnant females and elderly (question numbers 2, 4, 10, 12). The patients as well as their attendants did not differ significantly in the responses given to the queries. Maximum number of patients received knowledge regarding ECT from doctors; few had attained it from other sources like internet. Conclusions: The study is a preliminary one and emphasizes the need for better standardized questionnaire for proper assessment. It also gives us an insight into lack of knowledge among patients and their attendants regarding ECT.